Stitch Head : The Pirate's Eye - Bass, Guy; Illustrated by Williamson, Pete (London Stripes, 2012)
Someone small is about to set sail on a big adventures. Join a mad professor's forgotten creation as he prepares for an almost-life on the high seas.
Include Ilustrations
Keywords: Monsters -- Juvenile fiction -- Monsters